2D and 3D Shapes of Elliptical Galaxies NGC 1199, 1395 and NGC 1549 - Arun Kumar Diwakar, Aloke Verma, Avinash Singh, Tripti Richhariya, Ekta Chandrawanshi, Laxmikant Chaware (Mathematical Statistician and Engineering Applications, 2023)
Photometric data from the literature is combined with triaxial mass models to derive 2D and 3D shapes of the light distribution of elliptical galaxies NGC 1199; 1395 and 1549. The inferred shape variation in given by a Bayesian probability distribution, assuming a uniform prior. The likelihood of obtaining the data is calculated by using ensemble of triaxial models. We apply the method to infer the shape variation of a galaxy, using the ellipticities and the difference in the position angles at two suitably chosen points from the profiles of the photometric data. Best constrained shape parameters are found to be the short to long axial ratios at small and large radii, and the absolute values of the triaxiality difference between these radii.